Frutos de la cooperacion nacional e internacional. El caso de convenio IDIAP/FCA/CIAT en Panama (1982-1988) - Martinez, C.P.=700 1 Espinosa, E.; Berrio, L.E.; Jaen, A.E.; Batista, E.; Gaona, J.; Gutierrez, H.
(Es, En)
ilus., 11 ref.
Keywords: ORYZA SATIVA; SELECCION; GERMOPLASMA; ACUERDOS COMERCIALES; ACUERDOS INTERNACIONALES; PANAMA